Mastication Profile and Alternative Healthy Mastication Model using Coconut Frond Shaving in Karo Women - Ulina Karo-Karo (Journal of Global Pharma Technology, 2020)
Introduction: The use of tobacco in mastication activity has been widely known throughout the world. In China, the prevalence of mastication activity using betel leaves during student age is around 3.9%. Karo women in Deli Serdang are one of the population in Indonesia whose known have mastication habit since a long time ago. This study aimed to know the profile of the mastication model in Karo women as a primary aim and introduce coconut frond shavings mastication as the healthy mastication model. Method: This research was a combination of qualitative-quantitative diffusion of innovations research, with four stages, those are: diagnosis of action, plan of action, implementation of actions, and evaluation of an action. Results: Systolic blood pressure, diastole blood pressure, and blood sugar levels among coconut fronds chewers were less than tobacco chewers. This data also showed statistically different among two variables (p